MODEL IMPLEMENTASI KEBIJAKAN PENGEMBANGAN ILMU BERPARADIGMA ISLAMI DALAM AKSELERASI PENCAPAIAN VISI DAN MISI KONVERSI IAIN SUSQA PEKANBARU KE UIN SUSKA RIAU - Amri Darwis (JURNAL TARBIYAH, 2014)
This article is the results of the research about “Evaluation of policy of developing Islamic paradigm knowledge”. It is the ultimate mision of converting Islamic Higher Education which has a status as State Islamic Institution (IAIN) to be State Islamic University (UIN). Because of the image of IAIN is considered trapped in the dicotomy of knowledge, then it was more focused on Islamic studies and seems ignoring the seculer studies. Therefore, the new mision is fostered “the Integration of Knowledge and Islam” This paper is the policy research by reviewing the sides of the problems on the fields particularly the policy implementation model of developing Islamic paradigm of knowledge as the ultimate mision of converting IAIN to UIN Suska Riau that still left behind other elements which have progress very rapidly. The form of this research is developing model. After being analyzed various models of implementation of policy. Thus, accordance with the method of research, the model treatment have been tested in the faculty of Education and Teacher Training, and Faculty of Social Science and Economy Faculty. The results, from various models developed such as Top Down model, Buttom up, and Hybridge, Hybridge model is considered more effective and efficient to be applied. While, the main contraint from interview results conducted at the faculty level evidently have no any models, guidances, and instructions about developing islamic paradigm of knowledge, either at the general faculties and religious faculties.